Influence of slope shape on susceptibility to erosion in the Rio Claro watershed (Santa Rita do Passa Quatro, SP) - Basilio, Thamiris Cristina Costa; Fujimoto, Jaqueline Tomiê; Lopes, Thiago; Asciutti, Gustavo Augusto Mendonça; Lorandi, Reinaldo; de Lollo, José Augusto [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2019)
Erosion, known as a phenomenon that causes serious consequences to the physical environment, has become a global concern and the focus of many studies in order to prevent or control its effects. The catchment area of Rio Claro, located in the northeastern part of the state of São Paulo, consists predominantly of unconsolidated sandy texture materials and comprises an area of 251.91km2. The aim of this work was to investigate the influence of slope shapes on the analysis of susceptibility to the accelerated erosion of this basin at a 1:50,000 scale, by comparing two methods: Analytical Hierarchical Process (AHP) Technique and Weighted Sum (WS). Intermediate and thematic cartograms were generated from a pre-existing database. The regions with slopes between 2 and 10% comprise 1.55km2 and are characterized as medium concave and convex hills, with the presence of unconsolidated materials corresponding mainly to the Quaternary and Tertiary Formations, where there is a predominance of large active erosions. The results show disseminated erosion processes in areas classified as low susceptibility and very low according to the two techniques. The concentration of the erosion processes is controlled by the shape of the slopes, particularly in the areas of medium hills with concave profiles, with sandy soil profiles and low compactness. In addition to the influence of sandy texture and low compactness of soils, concentration of erosive processes is mainly controlled slope shape. Major number of erosive processes occurs in concave divergent hills areas, while the highest densities of erosive processes are located in areas of convex divergent hills and, secondarily, in rectilinear divergent hills.
Influência da Forma das Encostas na Suscetibilidade à Erosão na Bacia Hidrográfica do Rio Claro (Santa Rita do Passa Quatro, SP)
Keywords: Hydrographic basin; Shape of slopes; Susceptibility to erosion